Development of Interactive E-Module Based on Problem Based Learning to Improve Students' Higher Order Thinking Skills in Acid Base Material - Feby Khansa Ketaren; Haqqi Annazili Nasution (Universitas Lampung, 2025)
Development of Interactive E-Module Based on Problem Based Learning to Improve Students' Higher Order Thinking Skills in Acid Base Material. The low ability of students' Higher Order Thinking Skills in understanding chemical concepts, especially in acid-base material, is one of the challenges in the learning process. This material is often abstract and requires a deep understanding of the concept, so innovative learning media are needed to stimulate critical thinking, analytical, and problem-solving skills. Therefore, this study aimed to determine the improvement of students' HOTS on acid-base material after using interactive e-modules based on Problem-Based Learning. This study is a development research using the 4D development model (Define, Design, Develop, and Disseminate). The research sample was taken randomly, consisting of 32 students of class XI Sains A7 at MAN 1 Medan. The research instruments included validation sheets from material experts, media experts, teacher and student response questionnaires, and tests given before (pre-test) and after (post-test) the use of interactive e-modules. The validation results showed that the developed e-module was in the category of being suitable for use. The average percentage of validation from material experts was 82.7%, media experts 85.55%, chemistry teacher responses were 84.5%, and students' responses were 87.45%. Effectiveness analysis was carried out using normality test, one sample t-test, and N-gain test. The normality test showed that the data was normally distributed. The results of the one sample t-test showed a significance value <0.001. While the results of the N-gain test showed an average value of 0.69 which is included in the moderate increase category. Based on these results, the interactive e-module based on Problem Based Learning developed is declared valid, practical, and effective in improving students' higher order thinking skills (HOTS) in acid-base material. Therefore, it is suitable for use as an alternative learning media in acid-base chemistry learning at the high school level.